1995
DOI: 10.1016/s0008-6363(96)88525-7
|View full text |Cite
|
Sign up to set email alerts
|

Acadesine reduces myocardial infarct size by an adenosine mediated mechanism

Abstract: Acadesine reduces infarct size by an adenosine mediated mechanism, but this cardioprotective action is not associated with significantly augmented interstitial fluid adenosine levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…First, AICAR is an analogue of adenosine that in some studies has been reported to have physiological actions in the heart via adenosine receptor stimulation. 30 However, adenosine-induced vasodilatation in our model develops within 1 minute (E. Eringa, unpublished results) and is endothelium independent. Furthermore, the adenosine receptor blocker 8-phenyltheophylline did not inhibit AICARinduced vasodilation in isolated resistance arteries (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…First, AICAR is an analogue of adenosine that in some studies has been reported to have physiological actions in the heart via adenosine receptor stimulation. 30 However, adenosine-induced vasodilatation in our model develops within 1 minute (E. Eringa, unpublished results) and is endothelium independent. Furthermore, the adenosine receptor blocker 8-phenyltheophylline did not inhibit AICARinduced vasodilation in isolated resistance arteries (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…One might therefore conclude that intravascular adenosine is critical in mediating cardioprotection. This is further supported by studies demonstrating reduced infarct size or contractile dysfunction with adenosine-regulating agents (155,314), which fail to modify interstitial adenosine. Large-molecular-weight adenosine agonists restricted to the vascular compartment also elicit cardioprotection (277).…”
Section: Importance Of Intravascular Versus Interstitial Adenosinementioning
confidence: 77%
“…It is interesting to note that a meta-analysis of clinical studies using AICAR in the setting of coronary artery bypass grafting demonstrated modest reductions in early cardiac death, myocardial infarction, and the need for LV assist device support (48). Historically, AICAR was developed as a drug (acadesine) designed to increase extracellular adenosine concentrations and adenosine receptor stimulation in ischemic tissue (49). Although not recognized at the time, it is possible that activation of AMPK may have played a role in these beneficial effects.…”
Section: Figurementioning
confidence: 99%